Analisis Perbandingan Karakteristik Perkerasan Jalan Raya AC-BC Menggunakan Abu Sekam Padi Sebagai Filler Alternatif - Setiawan, Beny (Jurnal Teknik Industri Terintegrasi (JUTIN), 2022)
One of the factors for the advancement of the economy of a region is due to smooth transportation routes, because with smooth transportation routes the process of selling, buying and exchanging goods can be carried out. Highway pavement is an important factor in supporting the development of transportation infrastructure, asphalt concrete mixture on road pavement requires filler material as a modification to increase strength and fill empty cavities in the pavement constituent structure. Rice husk contains ± 90% -98% silica after undergoing complete combustion, which is expected from this study, this content can provide good benefits for the AC-BC pavement building material. The results of this study can draw the conclusion that the characteristics of the AC-BC pavement using rice husk ash for each variation do not pass the Cavity points in the mixture (VIM) and Cavity in mineral aggregate (VMA) which have been determined by the Highways Guidelines, while for other characteristics of the test specimens for each variation passed the specifications. Comparison of the characteristic values ??of each test object according to the very significant variation, the value of each characteristic increases with the increase in the amount of rice husk ash added.